Biogeographical patterns of Pinguicula L. (Lentibulariaceae) in the Americas revealed by endemicity and habitat suitability analyses - Domínguez, Yoannis [UNESP]; Temple, Paul; Pančo, Ivan; Miranda, Vitor F.O. [UNESP] (Elsevier, 2024)
Butterworts (Pinguicula L.) exhibit a widespread and highly discontinuous distribution in the American continents that host 87 species showing a high level of endemism. To increase our understanding of how such biogeographical patterns originated, we searched for areas of endemism and modelled the suitable habitats for three functional groups of species: temperate heterophyllous, tropical heterophyllous and homophyllous, including their respective geographic subgroups. This approach enabled us to analyse potential distribution changes over time, from the Last Interglacial to the present, and to compare range shifts with the current known distribution in the study area. Through an endemicity analysis, we identified three areas of endemism within the Neotropical region, encompassing two centres of endemism: the Antillean subregion and the Mexican Transition Zone. The models we developed demonstrated high accuracy in predicting the suitable habitats for each group (AUC = 0.906–0.982; TSS = 0.682–0.985). Different sets of bioclimatic variables played a significant role in influencing the potential distribution of Pinguicula functional groups, resulting in differential range shifts from the LIG to the present. Temperate heterophyllous and homophyllous species from southeastern North America, the Caribbean and northern South America experienced severe range contraction during the LGM. Conversely, tropical heterophyllous and homophyllous species from northern South America exhibited range expansion from the LGM to the present. Stable suitable habitats identified in Mexico and eastern Cuba throughout the analysed time periods were closely associated with the two centres of endemism, likely serving as refugia. In contrast, other suitable areas displaying climatic stability were not retrieved as current endemic-rich regions. Therefore, these centres of endemism represent key areas for the conservation of Pinguicula diversity in the Americas, as they can promote the survival of lineages under future climatic variations.
Keywords: Antillean subregion; Butterwort; Endemism; HSMs; Maxent; Mexican transition zone; Potential distribution modelling